Adsorption of Cadmium (Cd) Metal in Solution Using Pofa-Based Zeolite (Palm Oil Fly Ash) - Darmayanti, Lita; Indriani, Lisa (EduChemia: Jurnal Kimia dan Pendidikan, 2024)
Cadmium is one of the heavy metals with high toxicity that can harm human health and the environment. A commonly used method to remove heavy metals is adsorption. One of the widely used adsorbents is zeolite, which is composed primarily of silica and alumina. Palm oil fly ash (POFA) is a waste from palm oil mills that is rich in silica and alumina so that it can be used as a basic material for zeolite. This research aims to study the factors that affect the adsorption process of Cd metal using zeolite synthesized from POFA and determine the kinetics and isotherms of adsorption. The factors observed were pH (3, 4, 5, 6; 7), adsorbent dosage (1, 1.5, 2, 2.5, 3 g/l), contact time (5, 10, 15, 30, 60, 90, 120, 150, 180 min), and initial concentration of Cd metal (2, 4, 6, 8, 10, 15 mg/L). Adsorbent characterization was performed by XRF and XRD analysis. The results showed that pofa-based zeolite can remove Cd metal with an efficiency above 95%. The adsorption process can follow well the pseudo-second-order kinetics model and both Langmuir and Freundlich isotherm models with a maximum adsorption capacity of 64.58 mg/g. The zeolite synthesized from POFA can remove Cd metal well and has the potential to be developed into an adsorbent